Pembinaan Kecerdasan Spiritual di Pondok Pesantren Suryalaya - Khoirunnisa, Hawa; Syahidin, Syahidin; Supriadi, Udin (PT. Student Rihlah Indonesia, 2023)
This research is motivated by issues contained in contemporary PAI learning, one of which is the lack of spirituality; both informative and transformative in schools. This study aims to find solutions to PAI problems through the enrichment of existing learning models by adding learning methods, strategies, and approaches used by TQN in Suryalaya in order to create a more effective and efficient learning model for spiritual transformation in PAI learning in the classroom. Using a qualitative approach, this study used a descriptive method; Data collection techniques through observation, interviews, and documentation. With the use of these three techniques, the data found were validated using triangulation techniques. The findings of this study are that the spiritual intelligence development process that occurs at TQN Suryalaya focuses on the practice of teachings and experiences and the implications of the spiritual intelligence coaching model that can be applied in the classroom in the form of increased integration between science and charity, as well as the strong influence of an educator's example in transformative education.